Bottom‐up Fabrication and Atomic‐Scale Characterization of Triply Linked, Laterally π‐Extended Porphyrin Nanotapes. (14th June 2021) - Sun, Qiang; Mateo, Luis M.; Robles, Roberto; Lorente, Nicolas; Ruffieux, Pascal; Bottari, Giovanni; Torres, Tomás; Fasel, Roman
Abstract: Porphyrin nanotapes (Por NTs) are promising structures for their use as molecular wires thanks to a high degree of π‐conjugation, low HOMO—LUMO gaps, and exceptional conductance. Such structures have been prepared in solution, but their on‐surface synthesis remains unreported. Here, meso–meso triply fused Por NTs have been prepared through a two‐step synthesis on Au(111). The diradical character of the on‐surface formed building block PorA2, a phenalenyl π‐extended Zn II Por, facilitates intermolecular homocoupling and allows for the formation of laterally π‐extended tapes. The structural and electronic properties of individual Por NTs are addressed, both on Au(111) and on a thin insulating NaCl layer, by high‐resolution scanning probe microscopy/spectroscopy complemented by DFT calculations. These Por NTs carry one unpaired electron at each end, which leads to magnetic end states. Our study provides a versatile route towards Por NTs and the atomic‐scale characterization of such tapes. Abstract : Herein, we describe the first on‐surface preparation of porphyrin nanotapes (Por NTs) on a gold surface. Structural and electronic characterization reveals that the Por NTs carry one unpaired electron at each end, which leads to magnetic end states. This study provides an alternative and versatile route to the fabrication of Por NTs and a detailed atomic‐scale characterization of their structural and electronic properties.